Study on Economy and Dynamic Performance of LMD Thin Wheel Flange Tread - REN Jiwen; ZHAN Lingfeng; LIN Fengtao; ZHANG Qi (机车电传动)
Based on 8 times wheel profile measurement and wear tracking test of a CRH1 EMUs, and analysis of the main parameters such as flange thickness and equivalent taper, the thin wheel treads of the LMD series were designed. With dynamic software UM, the dynamic model of CRH1 EMUs was estabshed, the original tread and LMD thin wheel flange tread were compared on the following aspects: vehicle critical speed, the lateral stability of the frame, the stability of the vehicle body, the performance of small curve and turnout etc. The result showed that the economy of LMD thin wheel flange tread has a great improvement, and the dynamic indexes satisfy the operational requirements.